2017
DOI: 10.1111/imr.12566
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to “allergic inflammation”

Abstract: Allergic inflammation is a hallmark of pathology of type 2 inflammatory disorders, such as asthma, atopic dermatitis, rhinosinusitis, and food allergy. Eosinophilic inflammation and IgE-mediated hyperre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Allergen-specific CD4 + T helper type 2 (Th2) cells are pivotal players in causing and maintaining the allergic diseases as they specifically recognize the allergen and induce the subsequent development of allergic inflammation (16)(17)(18). DCs are essential antigen-presenting cells (APCs) that initiate immunity by stimulating and differentiating antigen-specific naive T cells (1,19).…”
Section: Introductionmentioning
confidence: 99%
“…Allergen-specific CD4 + T helper type 2 (Th2) cells are pivotal players in causing and maintaining the allergic diseases as they specifically recognize the allergen and induce the subsequent development of allergic inflammation (16)(17)(18). DCs are essential antigen-presenting cells (APCs) that initiate immunity by stimulating and differentiating antigen-specific naive T cells (1,19).…”
Section: Introductionmentioning
confidence: 99%
“…Allergic diseases in the upper and lower airways include asthma, allergic rhinitis, and nasal polyposis. In airway allergic reactions, antigens that have penetrated epithelial layers are engulfed by dendritic cells (DCs), inducing them to mature and migrate to the lymph nodes, where they activate naïve T cells into effecter T helper 2 (Th2) cells [6]. Cytokines such as interleukin-4 (IL-4), IL-5, and IL-13 are released from Th2 cells or type 2 innate lymphoid (ILC2) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several recent findings suggested that ILC2 play an important role in eosinophilic airway inflammation in mice that lack the ability to mount adaptive immune responses 14 , 15 . Th2 cells and ILC2 may contribute to distinct types of inflammation such as allergen-specific and non-specific allergic inflammation, respectively 16 . Th2 cells and ILC2s are the major source of Th2 cytokines in allergic asthma, and these cells may also collaborate in allergen-driven innate and adaptive type2-lung inflammation 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%